Effect of Oral Beta-Hydroxy-Beta-Methylbutyrate (HMB) Supplementation on Physical Performance in Healthy Old Women Over 65 Years: An Open Label Randomized Controlled Trial. - Linda Berton; Giulia Bano; Sara Carraro; Nicola Veronese; Simona Pizzato; Francesco Bolzetta; Marina De Rui; Elena Valmorbida; Irene De Ronch; Egle Perissinotto; Alessandra Coin; Enzo Manzato; et al. (PLoS ONE, 2015)
Although older people are particularly liable to sarcopenia, limited research is available on beta-hydroxy-beta-methylbutyrate (HMB) supplementation in this population, particularly in healthy subjects. In this parallel-group, randomized, controlled, open-label trial, we aimed to evaluate whether an oral supplement containing 1.5 g of calcium HMB for 8 weeks could improve physical performance and muscle strength parameters in a group of community-dwelling healthy older women. Eighty healthy women attending a twice-weekly mild fitness program were divided into two equal groups of 40, and 32 of the treated women and 33 control completed the study. We considered a change in the Short Physical Performance Battery (SPPB) score as the primary outcome and changes in the peak torque (PT) isometric and isokinetic strength of the lower limbs, 6-minute walking test (6MWT), handgrip strength and endurance as secondary outcomes. Body composition was assessed with dual-energy X-ray absorptiometry (DXA) and peripheral quantitative computerized tomography (pQCT). The mean difference between the two groups on pre-post change were finally calculated (delta) for each outcome. After 8 weeks, there were no significant differences between the groups’ SPPB, handgrip strength or DXA parameters. The group treated with HMB scored significantly better than the control group for PT isokinetic flexion (delta = 1.56±1.56 Nm; p = 0.03) and extension (delta = 3.32±2.61 Nm; p = 0.03), PT isometric strength (delta = 9.74±3.90 Nm; p = 0.02), 6MWT (delta = 7.67±8.29 m; p = 0.04), handgrip endurance (delta = 21.41±16.28 s; p = 0.02), and muscle density assessed with pQCT. No serious adverse effects were reported in either group. In conclusion, a nutritional supplement containing 1.5 g of calcium HMB for 8 weeks in healthy elderly women had no significant effects on SPPB, but did significantly improve several muscle strength and physical performance parameters.ClinicalTrials.gov NCT02118181.